A guide to econometrics - Kennedy, Peter (MT Press, 1998)
This is the perfect (and essential) supplement for all econometrics classes--from a rigorous first undergraduate course, to a first master's, to a PhD course.Explains what is going on in textbooks full of proofs and formulas, offers intuition, skepticism, insights, humor, and practical advice (dos and don’ts), contains new chapters that cover instrumental variables and computational considerations, includes additional information on GMM, nonparametrics, and an introduction to wavelets